Nilai-Nilai Pendidikan Islam Dalam Kitab Taisir Al-Khallaq Karya Syekh Hafidz Hasan Al-Mas’udi Dan Relevansinya Terhadap Pendidikan Moral Masa Kini - Rosyid, Muhammad Iqbal; Zuhdi, Ahmad; Munawaroh, Hidayatu (Faidatuna, 2024)
The book Taisir Al-Khallaq Fi 'Ilmi Al-Akhlaq by Sheikh Hafidz Hasan Al-Mas'udi is a yellow book which contains guidelines for Muslims in living their daily lives. Even though it is famous for its moral studies, it contains Islamic educational values ​​and its relevance to today's moral education. This research aims to determine the concept of Islamic and moral education, the values ​​of Islamic education in the book Taisir Al-Khallaq Fi 'Ilmi Al-Akhlaq and its relevance to today's moral education. This research uses a descriptive qualitative research approach, where the type of research is literature. The data collection technique uses the documentation method. Then, data sources were obtained from primary data sources, namely the book Taisir Al-Khallaq and secondary (books, journals and other sources). The data analysis technique uses content analysis. The results of this research show that; 1) the concept of Islamic education includes three main aspects, namely al-tarbiyah, al-ta'lim, and al-ta'dib which means the teaching process. Meanwhile, the concept of moral education is based on Islamic education itself. 2) the values ​​of Islamic education contained in this book are in the form of aqidah values, worship values ​​and moral values. 3) the values ​​of Islamic education in this book are very relevant to today's moral education, because they both aim to form human beings who are moral, have noble character, and make them obedient and obedient servants of Allah SWT.